A dual function theranostic agent for near-infrared photoacoustic imaging and photothermal therapy - Upputuri, Paul Kumar (2016)
Theranostic, defined as combining diagnostic and therapeutic agents, has attracted more attention in biomedical application. It is essential to monitor diseased tissue before treatment. Photothermal therapy (PTT) is a promising treatment of cancer tissue due to minimal invasion, unharmful to normal tissue and high efficiency. Photoacoustic tomography (PAT) is a hybrid nonionizing biomedical imaging modality that combines rich optical contrast and high ultrasonic resolution in a single imaging modality. The near infra-red (NIR) wavelengths, usually used in PAT, can provide deep penetration at the expense of reduced contrast, as the blood absorption drops in the NIR range. Exogenous contrast agents with strong absorption in the NIR wavelength range can enhance the photoacoustic imaging contrast as well as imaging depth. Most theranostic agents incorporating PAT and PTT are inorganic nanomaterials that suffer from poor biocompatibility and biodegradability. Herein, we present an benzo[1,2-c;4,5-c’] bis[1,2,5] thiadiazole (BBT), based theranostic agent which not only acts as photoacoustic contrast agent but also a photothermal therapy agent. Experiments were performed on animal blood and organic nanoparticles embedded in a chicken breast tissue using PAT imaging system at ~803 nm wavelengths. Almost ten time contrast enhancement was observed from the nanoparticle in suspension. More than 6.5 time PA signal enhancement was observed in tissue at 3 cm depth. HeLa cell lines was used to test photothermal effect showing 90% cells were killed after 10 min laser irradiation. Our results indicate that the BBT - based naoparticles are promising theranostic agents for PAT imaging and cancer treatment by photothermal therapy.